2021
DOI: 10.1101/2021.03.05.21252520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification of the spread of SARS-CoV-2 variant B.1.1.7 in Switzerland

Abstract: In December 2020, the United Kingdom (UK) reported a SARS-CoV-2 Variant of Concern (VoC) which is now coined B.1.1.7. Based on the UK data and later additional data from other countries, a transmission advantage of around 40-80% was estimated for this variant. In Switzerland, since spring 2020, we perform whole genome sequencing of SARS-CoV-2 samples obtained from a large diagnostic lab (Viollier AG) on a weekly basis for genomic surveillance. The lab processes SARS-CoV-2 samples from across Switzerland. Base… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…Several studies using other methods have similarly found D614G and B.1.1.7 to each have a selective advantage over other variants circulating contemporaneously [10, 19, 3, 12, 2]. In contrast, however, van Dorp et al [35] found no support for a selective advantage of any of the variants they tested, including D614G.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies using other methods have similarly found D614G and B.1.1.7 to each have a selective advantage over other variants circulating contemporaneously [10, 19, 3, 12, 2]. In contrast, however, van Dorp et al [35] found no support for a selective advantage of any of the variants they tested, including D614G.…”
Section: Discussionmentioning
confidence: 94%
“…Although phylogenetic replication is an appropriate requirement in many situations, it is too conservative for identifying variants of concern on the timescale at which they emerge. Instead, to test for a selective advantage of variants that have arisen only once, power can be obtained from fitting explicitly epidemiological models within one location (e.g., our stochastic model, and others [19, 3, 12, 2]) or looking for consistent effects in multiple locations with largely-distinct conditions (e.g., our isotonic regression and population genetic models, and Korber et al [10]).…”
Section: Discussionmentioning
confidence: 99%
“…Washington et al estimated a 35–45% increase using data from the United States of America using Volz’s method (Washington et al, 2021). Chen et al estimated 49–65% increase in reproduction number using data from Switzerland also under the constant R assumption (Chen et al, 2021). Due to the high transmissibility the B.1.1.7 strain, strong control measure such as lockdown was taken when the strain was introduced (Davies et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Volz et al estimated a 50-100% increase in using data from England (Volz et al 2021), while Washington et al estimated a 35-45% increase using data from the United States using Volz's method (Washington et al 2021). As well, Chen et al estimated a 49-65% increase using data from Switzerland (Chen et al 2021). Strong control measures including movement restrictions and ban on meeting and event were taken to respond to the introduction of a strain with high transmissibility.…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of B.1.1.7 associated mutations reached quickly up to 76.92% (4). The B.1.1.7 strains not only have high transmissibility (2), quickly spread to many countries (5)(6)(7)(8), but also increase risk of death (9,10). It has been documented that S:p.N501Y (11,12) and S:p.D614G (13,14) increase the viral transmissibility, and S:p.P681H occurs on the spike S1/S2 cleavage site (15).…”
mentioning
confidence: 99%